2002
DOI: 10.1093/pcp/pcf078
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of S-adenosylmethionine Decarboxylase Activity is a Major Cause for High-Temperature Inhibition of Pollen Germination and Tube Growth in Tomato (Lycopersicon esculentum Mill.)

Abstract: Possible involvement of impaired polyamine biosynthesis in the poor performance of tomato pollen (Lycopersicon esculentum Mill.) at high temperatures was investigated. Incubation of pollen at 38 degrees C suppressed the increase of S-adenosylmethionine decarboxylase (SAMDC) activity in germinating pollen with little influence on arginine decarboxylase activity. Consequently, spermidine and spermine content in the pollen did not increase at 38 degrees C, while putrescine content increased at both 25 degrees C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…After centrifugation, free polyamines in the supernatant were dansylated with dansyl chloride (10 mg ml Ϫ1 acetone) and quantified via HPLC with 1,6-hexanediamine as the internal standard, as described by Song et al (2002). Chlorophylls in leaves were extracted with 80% (v/v) acetone and quantified spectrophotometrically by the method of Arnon (1949).…”
Section: Chemical Analysismentioning
confidence: 99%
“…After centrifugation, free polyamines in the supernatant were dansylated with dansyl chloride (10 mg ml Ϫ1 acetone) and quantified via HPLC with 1,6-hexanediamine as the internal standard, as described by Song et al (2002). Chlorophylls in leaves were extracted with 80% (v/v) acetone and quantified spectrophotometrically by the method of Arnon (1949).…”
Section: Chemical Analysismentioning
confidence: 99%
“…43) SAMDC is the key enzyme in PA biosynthesis that decarboxylates Sadenosylmethionine and supplies an aminopropyl moiety to putrescine and spermidine. 44) Low activity of SAMDC is a major cause of poor performance of tomato pollen germination at high temperatures. To our knowledge, no prior study has elucidated the relationship between PA and microspore development in the rice plant.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggested that heat stress decreased the level of polyamines. Indeed, an incubation of pollen at 38 °C during 4 h lowered the content of spermidine and spermine whereas the content of putrescine increased and these changes correlated with a decrease of pollen germination (Song et al 2002). Adding spermidine or spermine to the medium restored the level of pollen germination.…”
Section: Polyaminesmentioning
confidence: 94%
“…Therefore, pollen isolated in such a way needs to be considered as imbibed pollen (with analogy to seed). Although isolation in a solution is the most widespread method, isolation of dry mature pollen without solution is also found in literature (Song et al 2001, Song et al 2002. We called this isolation method flower vibrating with further pollen lyophilisation (VL).…”
Section: Imbibed Versus Dry Pollenmentioning
confidence: 99%
See 1 more Smart Citation